Tanzihu Ulil Adyaan Min Tadhlil Gulaamul Qaadiyaan (Karangan Sayid Husain Syahab) - Sayuti, Mohd. (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2005)
This article discusses Ahmadiyah Qodiyan, an Islamic sect established at the end of 19h century in India, in the view of Sayyid Husein Shahabs Thoughts. He defeated Mirza Ghulam Ahmads thoughts on the debate about the seal of the prophet hood that Muhammad is the true seal of the ever revealed prophets. This discourse is to response to the Qrannically widespread ideas bringing about the decrease of the faith of the believers in all aspects of their very life. This discouse is still very actual today, as now, there happens some movements to forbid Ahmadiyah from its development in Indonesia.